Cover Picture: Amination of meso‐Bromoporphyrins and 9‐Haloanthracenes with Diarylamines Catalyzed by a Palladium–PEPPSI Complex (Asian J. Org. Chem. 12/2013). Issue 12 (December 2013) - Suzuki, Yuko; Fukui, Norihito; Murakami, Kei; Yorimitsu, Hideki; Osuka, Atsuhiro
<x xml:space="preserve">Abstract</x> A large number of triarylamine‐based functional devices have been reported. However, efficient routes to bulky triarylamines are still underdeveloped. In their Full Paper on page 1066 ff., Hideki Yorimitsu, Atsuhiro Osuka and co‐workers report a very efficient palladium‐catalyzed amination of bulky aryl halides. The reactions are applicable to meso‐bromoporphyrins and 9‐haloanthracenes with a wide variety of diarylamines. Commercially available and air‐stable Pd‐PEPPSI complexes that have N‐heterocyclic carbenes as ligands are the most catalytically active in this reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>